Pengenalan Wawasan Digital Marketing Bagi Guru SMK N 1 Labuhan Maringgai, Lampung Timur - Almira Devita Putri; Heri Kuswoyo; Ingatan Gulo; E. Ngestirosa; Ellisa Ghina Febrina (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2023)
Digital marketing is a product promotion activity in the form of goods or services using social networks so as to contribute to marketing activities. However, Pandemi Covid-19 which has passed is a starting point for changes in education in Indonesia and even the world that causes schools and teachers in Indonesia must switch to the learning and teaching system digitally. The situation of Post Pandemic Covid-19 has made the activity carried out digitally as a thing that is definitely used today. Therefore, the community service (PKM) of the University of Indonesia is a facilitator and an event for schools, especially teachers to be able to learn digital marketing in depth not only in technical aspects but also in terms of its use in the process of teaching and learning activities. Community service was carried out at SMKN 1 Labuhan Maringgai, Lampung Province. This is done with the aim of opening the teacher's insight in carrying out a digital marketing process. Not only that, through this activity also gave a presentation on how to build a business in the digital era by looking at the potential that exists in Labuhan Maringgai. Thus, the teacher is expected to be able to contribute not only to themselves and their families, but for students and the community.